Climate change, sustainable development, and human security : a comparative analysis - Vajpeyi, Dhirendra K. (Lexington Books, 2013)
The main focus of the book is to analyze pros and cons of the climate change debate among scholars, policy makers and scientist, and its impact on human security in various countries.